The divine states ("brahmaviharas") in managerial ethical decision-making in organisations in Sri Lanka an interpretative phenomenological analysis - Jayawardena-Willis, Thushini S.; Pio, Edwina 1955-; McGhee, Peter (2021)
Ethical decision-making (EDM) theories in behavioural ethics management have been developed through the social sciences, psychology, social psychology, and cognitive neurosciences. These theories are either cognitive, non-cognitive or an integration of both. Other scholars have recommended redefining what ethical means through moral philosophy and theology. Buddhism is a religion, a philosophy, a psychology, an ethical system and an art of living. The divine states (i.e. loving-kindness, compassion, sympathetic joy, and equanimity) in Buddhism are virtues that could be developed by anyone regardless of their religion or non-religion through Buddhist meditation. They are so called because they enable individuals to develop ‘God-like qualities’. The theoretical insights of the divine states indicate how to eliminate negative emotions, such as anger, fear, delusion and envy, by cultivating love and compassion towards both the self and others. Accordingly, this paper contributes to EDM by redefining what ethical means through the meanings managers who practise Buddhist meditation assign to divine states in their lived experience of EDM in organisations in Sri Lanka. The sample consisted of 17 Buddhists, 1 Hindu, 1 Muslim and 1 no-religion. Data were collected using semi-structured in-depth interviews and was analysed with IPA. The findings indicated that how the managers made meaning of an ethical decision was influenced by their loving-kindness, compassion, sympathetic joy and equanimity. The findings also indicated that the managers justified the reasons for their decisions subsequently through the benefits to themselves as well as their employees. Accordingly, this study supports the view that EDM is an integrated approach.
Keywords: Buddhism; Divine states (brahmaviharas); ethical decision-making; Sri Lanka; Aufsatz in Zeitschrift